Real-world data on the effects of colistin sulfate and polymyxin B sulfate in the treatment of pneumonia induced by CR-GNB - Di Liu; Fang Jie; Yongjie Ding; Hongping Qu; Dechang Chen; Jie Huang (Journal of Infection in Developing Countries)
Introduction: The aim of this study was to compare the efficacy and safety of colistin sulfate (CS) with polymyxin B sulfate (PMB) in the treatment of pneumonia induced by carbapenem-resistant Gram-negative bacteria (CR-GNB).